Social contract - Locke,John; Hume,David; Rousseau,Jean-Jacques (London)
Thas haunted the generations (it was current in the days of Plato, during the fourth century B.C., and it still flutters in the pages of Herbert Spencer's The Man versus the State at the end of the nineteenth century of our era), may be criticized on various grounds. The critic may urge that it was mechanical, and not organic, in its interpretation of political life; juristic, and not ethical, in its rationale of political obligation; a priori, and not historical, in its explanation of political society and political authority. The criticisms have their justice. The theory of the Social Contract could flourish only in an age, or 'climate', of thought in which the historical sense (the legacy left by the Romantic movement to the historians of the nineteenth century) was still imperfect and undeveloped. But if it was unhistorical, the theory was still historic-and historic in more than one sense.
Keywords: Political Science